Status of the GERDA Experiment at the Laboratori Nazionali del Gran Sasso - R. Brugnera; A. Garfagnini (Advances in High Energy Physics)
The Germanium Detector Array (Gerda) is a low background experiment at the Laboratori Nazionali del Gran Sasso (LNGS) of the INFN designed to search for the rare neutrinoless double beta decay (0νββ) of 76Ge. In its first phase, high purity germanium diodes inherited from the former Heidelberg-Moscow and Igex experiments are operated “bare” and immersed in liquid argon, with an overall background environment of 10−2 cts/(keV·kg·yr), a factor of ten better than its predecessors. Measurements on two-neutrino double beta decay (2νββ) giving T1/22ν=(1.88±0.10)×1021 yr and recently published background model and pulse shape performances of the detectors are discussed in the paper. A new result on 0νββ has been recently published with a half-life limit on 0νββ decay T1/20ν>2.1×1025 yr (90% C.L.). A second phase of the experiment is scheduled to start during the year 2014, after a major upgrade shutdown. Thanks to the increased detector mass with new designed diodes and to the introduction of liquid argon instrumentation techniques, the experiment aims to reduce further the expected background to about 10−3 cts/(keV·kg·yr) and to improve the 0νββ sensitivity to about T1/20ν>1.5×1026 yr (90% C.L.).